Alzheimer’s Disease Clinical Trials: Moving Toward Successful Prevention - Rafii, Michael S.; Aisen, Paul S. (CNS drugs, 2019)
Despite major academic and industry efforts, Alzheimer’s disease (AD) remains the only leading cause of death for which no disease-modifying treatment is available. Disappointing clinical trials over the last several years have led to a growing consensus on the need to intervene earlier in the disease process, before the onset of any clinical symptoms. However, drug development at this stage is challenging given the difficulty of assessing a therapeutic benefit in subjects who are, by definition, clinically healthy. The US FDA recently issued new draft guidance for trials in early AD, which revised the taxonomy of AD by recognizing four stages of the disease, including an expanded view of the predementia stage. These guidelines further advance regulatory support for clinical trials in earlier stages of AD. We discuss the basis for this change and the impact it may have on early-intervention AD trials as well as on stimulating the need for improved biomarkers and outcome measures that will be required for a disease-modifying drug to win approval.